Choline Based Surfactants Promote Cellular Uptake of Solid Lipid Nanoparticles into Lung and Breast Cancer Cells - Saadat, Maryam; Jafari, Sevda; Mahmoudian, Mohammad; Sarfraz, Muhammad; Khaleseh, Farnaz; Zakeri-Milani, Parvin; Shahbazi-Mojarrad, Javid; Valizadeh, Hadi (Current Nanoscience, 2025)
AimsThe aim of this study was to synthesize two positively charged surfactants Stearoylcholine and Oleoylcholine from choline or vitamin B4, saturated and mono-unsaturated fatty acids to modify solid lipid nanoparticles (SLNs) in order to enhance cancer cell uptake.MethodsThese surfactants were synthesized by using the esterification method and then SLN formulations of unmodified and modified SLNs containing docetaxel were prepared by emulsification technique. Cytotoxicity of the SLNs was investigated in A549 and MCF7 cancer cells and their cell uptake was assessed by using fluorescent microscope and flow cytometry.ResultsThe results of our study revealed that SLNs pose a mean particle size range of 69-133 nm with spherical morphology. In vitro release study demonstrated a slow-release pattern for all three kinds of DTX-loaded SLNs. Stearoylcholine-containing SLNs showed the highest cytotoxic effect on both cells while cytotoxicity of Oleoylcholine SLNs exhibited a dose-dependent manner which may be due to the effect of saturated and mono-unsaturated parts of surfactants. According to flow cytometric analysis, OC and SC containing SLNs showed the highest uptake into A549 and MCF7 cells, respectively.ConclusionIn conclusion, choline-based surfactants could effectively increase the A549 and MCF7 uptake of modified SLNs, which may be due to cationic surface, choline transporters, and special receptors and mediators.
Keywords: cationic surfactants